The effects of sentiments on the dollar rand (USD/ZAR) exchange rate - Mogotlane, Kgomotso Euginia (My University, 2017)
This journal paper seeks to review the effects of investor sentiments on the USD/ZAR currency pair. The paper will focus on major investor sentiments that had either a negative or positive impact on the exchange rate volatility of the USD/ZAR currency pair. The literature is limited to the period between 2008 and 2017 quarter one. This period is based on the endeavour to understand how investor sentiment impacts the two currency pairs under investigation; post the financial crisis to date. The choice of the currency pair is based on: that USA is one of South Africa’s significant trading partners, and that ZAR also trades heavily against the USD. Both the ZAR and the USD follow a floating exchange rate regime. As a result, the short-run drivers of both currency exchange rates may be attributed to: economic fundamentals, investor sentiments, speculative attacks, as well as structural and liquidity shocks. The purpose of this paper is to focus purely on investor sentiment. Moreover, investor sentiments are random and unexpected news or events. The study followed desktop research and engaged with documents sourced from public domain. The data set was drawn from Bloomberg terminal due to reliability. Academic literature was accessed from various publications, both in print and soft copy. Lastly, the discussion relating to evidence was sourced from Bloomberg terminal wired news series. The research output is thus aimed at investors, hedgers, arbitrageurs, speculators and end-users in the foreign exchange market. The outline of this paper is as follows: Section one is the introduction to the research. Section two is literature review. Methodology section follows on in chapter three. 2 Section four focuses on the data collection, while section five discusses the results. Lastly, section six concludes the research work. Keywords: South Africa, The United States of America, exchange rate, USD/ZAR exchange rate, sentiments, volatility.
MBA
Keywords: Foreign exchange rates -- South Africa. Stock price forecasting.